On a possible origin for the lack of old star clusters in the small magellanic cloud - Carpintero, Daniel Diego (2013)
We model the dynamical interaction between the Small and LargeMagellanic Clouds and their corresponding stellar cluster populations.Our goal is to explorewhether the lack of old clusters (≳7 Gyr) in the Small Magellanic Cloud (SMC) can be the result of the capture of clusters by the Large Magellanic Cloud (LMC) as well as their ejection due to the tidal interaction between the two galaxies. For this purpose, we perform a suite of numerical simulations probing a wide range of parameters for the orbit of the SMC about the LMC.We find that, for orbital eccentricities e ≥ 0.4, approximately 15 per cent of the SMC clusters are captured by the LMC. In addition, another 20-50 per cent of its clusters are ejected into the intergalactic medium. In general, the clusters lost by the SMC are the less tightly bound cluster population. The final LMC cluster distribution shows a spatial segregation between clusters that originally belonged to the LMC and those that were captured from the SMC. Clusters that originally belonged to the SMC are more likely to be found in the outskirts of the LMC. Within this scenario, it is possible to interpret the difference observed between the star field and cluster SMC age-metallicity relationships for ages ≳7Gyr.